Training and Practice Patterns in Cancer Rehabilitation: A Survey of Physiatrists Specializing in Oncology Care. Issue 2 (9th September 2019) - Sharma, Raman; Molinares‐Mejia, Diana; Khanna, Ashish; Maltser, Susan; Ruppert, Lisa; Wittry, Sarah; Murphy, Ryan; Ambrose, Anne Felicia; Silver, Julie K.
Abstract : Background: Cancer rehabilitation is an integral part of the continuum of care for survivors. Due to the increasing number of survivors, physiatrists commonly see cancer patients in their general practices. Essential to guiding the field is to understand the current training and practice patterns of cancer rehabilitation physicians. Objectives: To assess current trends in training and practice for cancer rehabilitation physicians, including the level of burnout among providers in this field. Design: Cross‐sectional descriptive survey study. Setting: Online survey. Participants: American physicians who are affiliated with the Cancer Rehabilitation Physician Consortium (CRPC) of the American Academy of Physical Medicine and Rehabilitation (AAPM&R). The CRPC is a group of cancer rehabilitation providers (both fellowship‐trained and not fellowship‐trained) with the mission of furthering cancer rehabilitation medicine through education, research, and networking. Methods: All CRPC physicians were invited to complete a voluntary and anonymous 43‐question online survey. The survey was conceived by a group of eight experts interested in providing additional information to the current literature regarding the training and practice in the cancer rehabilitation field. Main Outcome Measurements: Training, practice, opioid prescribing, and professional support. Results: Thirty‐seven of 50 physicians participated (response rate = 74%). Respondents were from various states, the three most common being New York (16%, n = 6), Texas (16%, n = 6), and Massachusetts (11%, n = 4). About 57% (n = 21) of the respondents were employed in an academic medical center and 73% (n = 27) reported their primary departmental affiliation was Physical Medicine and Rehabilitation (PM&R). Approximately 78% (n = 29) credited mentorship early in training for their interest in the field. More than half (54%, n = 20) either strongly agreed or agreed that cancer rehabilitation fellowship training is necessary for graduating physiatrists who plan to treat oncology patients/survivors. National PM&R meetings were the primary source of continuing education for 86% (n = 31). Sixty‐five percent (n = 24), strongly agreed or agreed that cancer rehabilitation physiatrists should know how to prescribe opioids, and 35% (n = 13) reported prescribing them when appropriate. About 54% (n = 20) rated their level of burnout as low or very low, and more than half (51%, n = 19) believed their burnout level was lower than physiatrists treating other rehabilitation populations. Conclusions: Cancer rehabilitation is a growing subspecialty in PM&R, and most physiatrists in general practice will treat many survivors—often for neurologic or musculoskeletal impairments related to cancer or its treatment. Cancer rehabilitation physicians perceive that they have relatively low levels of burnout, and early mentorship and fellowship training is beneficial. Professional conferences and mentorship are a primary source for continuing education. Level of Evidence: IV.